PROBLEMS AND SOLUTIONS IN TEACHING LISTENING SKILLS TO B1-LEVEL STUDENTS - Rakhmonov, Nodirjon; Xamidova, Dilnavozxon (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article discusses the challenges faced by B1-level students in learning listening skills and offers practical solutions to address these difficulties. The problems identified include limited vocabulary, difficulty understanding fast speech and varied accents, the challenge of listening for specific information, inconsistent practice, cultural context misunderstandings, and passive listening habits. Solutions proposed include pre-listening vocabulary preparation, gradual exposure to faster speech, targeted listening tasks, and incorporating diverse materials to keep students engaged. Active listening strategies, cultural background information, and consistent feedback are emphasized as critical to improving students’ listening comprehension.